2014
DOI: 10.2174/1874325001408010225
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Femoral Neck Fracture with a Minimal Invasive Surgical Approach for Hemiarthroplasty – Clinical and Radiological Results in 180 Geriatric Patients

Abstract: Purpose : The Direct Anterior Approach (DAA) is well established as a minimal access approach in elective orthopaedic hip surgery. For the growing number of elderly patients with femoral neck fractures treated with Bipolar Hip Hemiarthroplasty (BHH), only a few results do exist. The study shows the clinical and radiological outcome for 180 patients treated by a modified DAA with BHH.Materials and Methods : The data of 180 geriatric patients with medial femoral neck fractures were evaluated retrospectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…In a literature review on minimally invasive THA, Jung et al [ 62 ] reported consistently lower levels of pain and use of analgesics. The same effect has been documented after HA for FNFs in retrospective and prospective analyses [ 30 , 31 , 63 ], and this effect was also present in our data set, with patients in the AMIS-arm on average suffering lower levels of pain. However, the effect did not reach significance, unlike in previous studies [ 31 , 63 ], and must be interpreted with caution since the agreement between formal ratings and verbal expressions of pain or discomfort seems to decrease with advancing age [ 64 ], and the reliability with cognitive impairment might be additionally limited.…”
Section: Discussionsupporting
confidence: 89%
“…In a literature review on minimally invasive THA, Jung et al [ 62 ] reported consistently lower levels of pain and use of analgesics. The same effect has been documented after HA for FNFs in retrospective and prospective analyses [ 30 , 31 , 63 ], and this effect was also present in our data set, with patients in the AMIS-arm on average suffering lower levels of pain. However, the effect did not reach significance, unlike in previous studies [ 31 , 63 ], and must be interpreted with caution since the agreement between formal ratings and verbal expressions of pain or discomfort seems to decrease with advancing age [ 64 ], and the reliability with cognitive impairment might be additionally limited.…”
Section: Discussionsupporting
confidence: 89%
“…In this series, 83.8% of patients were ambulatory on postoperative day 1 and 94.6% were ambulatory before discharge. In contrast, Unger et al [38] describe a series of 180 patients who underwent hemiarthroplasty for femoral neck fracture with the direct anterior approach, and found a 7.3% rate of previous ambulatory patients needing a wheelchair for mobilization at discharge. Time to ambulation after surgery has been shown to be an independent predictor of pneumonia, delirium, and length of hospital stay, and it is possible that adopting a tissue-sparing approach such as SuperPATH may reduce these complications [39] .…”
Section: Discussionmentioning
confidence: 96%
“…Femoral neck fractures are serious injuries in elderly due to the increasing number of advanced age population and comorbidities, which is associated with extremely morbidity and mortality rates [1][2][3][4]. Lung infections, deep vein thrombosis, muscular dystrophy, and pressure ulcers are the leading causes of comorbidities [2].…”
Section: Introductionmentioning
confidence: 99%